Developing A Public Value Waste Management Framework in Traditional Market - Fauziah, Nike Mutiara; Fadlurrahman; Nugraha, Joko Tri; Mahendradi, RM. (Proceeding International Conference on Science and Engineering, 2020)
The growth of trade activity impacts on increasing waste volume. One of the waste problem that becomes the attention of government is waste management in traditional market. Waste problem besides being challenging, can also be an opportunity, as well as waste management in Traditional Markets. This paper aims to explore the public value management theory that can be applied to the practice of waste management in traditional market. This paper is a literature review by examining journals related to waste management and public value. The results of various literature reviews will be used to developing a framework for analyzing public value in waste management in traditional market. This paper focuses on the developing of public values in the waste management in traditional market that could be classified of several aspects which are basic legitimacy and support; operational capabilities and substantial value. The result of paper create a framework to a public value in waste management in traditional market. This framework will make a theoretical contribution to the study of public service management.